Behind the scenes of cyberbullying: Personal and normative beliefs across profiles and moral disengagement mechanisms - Francisco, Sofia (2022)
The first study aims to examine cyberbullying roles and their relation to personal and normative beliefs. For this purpose, a total of 404 7th to 9th grade students answered the Inventory of Observed Cyberbullying Incidents. For the second study, semi-structured interviews to 34 9th grade students were analysed based on the Social Cognitive Theory of Moral Agency, to understand which moral disengagement mechanisms were more frequent regarding cyberbullying scenarios. Results revealed that bystanders were the most common role. Regarding beliefs, the All type of involvement group considered cyberbullying to be less severe than Bystanders, Bystanders-Victims and No Involvement group. Moreover, they perceived that their peer group believed cyberbullying was less unfair than Bystanders and No Involvement group. The most used moral disengagement mechanisms were blaming the victim and euphemistic labelling regarding seriousness. Personal, normative beliefs, as well as moral disengagement mechanisms operating in cyberbullying should be considered when designing interventions.